Carcinogenicity Assessment of Daprodustat (GSK1278863), a Hypoxia-Inducible Factor (HIF)-Prolyl Hydroxylase Inhibitor. (February 2020) - Adams, David F.; Watkins, Mark S.; Durette, Luc; Laliberté, Josée; Goulet, Félix; Debien, Elaine; Frazier, Kendall S.; Mellal, Nacéra; Chen, Liangfu; Shi, Wei; Thomas, Roberta; Hu, Erding
Daprodustat (GSK1278863) is a hypoxia-inducible factor (HIF)-prolyl hydroxylase (PHD) inhibitor in development for treatment of anemia of chronic kidney disease. Daprodustat's biological activity simulates components of the natural response to hypoxia; inhibition of PHDs results in HIF stabilization and modulation of HIF-controlled gene products, including erythropoietin. The carcinogenic potential of daprodustat was evaluated in 2-year carcinogenicity studies in Sprague-Dawley rats and CD-1 mice, where once-daily doses were administered. The mouse study also included evaluation of daprodustat's 3 major circulating human metabolites. There were no neoplastic findings that were considered treatment related in either study. Exaggerated pharmacology resulted in significantly increased red cell mass and subsequent multiorgan congestion and secondary non-neoplastic effects in both species, similar to those observed in chronic toxicity studies. In rats, these included aortic thrombosis and an exacerbation of spontaneous rodent cardiomyopathy, which contributed to a statistically significant decrease in survival in high-dose males (group terminated in week 94). Survival was not impacted in mice at any dose. Systemic exposures (area under the plasma concentration–time curve) to daprodustat at the high doses in rats and mice exceed predicted maximal human clinical exposure by ≥143-fold. These results suggest that daprodustat and metabolites do not pose a carcinogenic risk at clinical doses.